The StBBX24 protein affects the floral induction and mediates salt tolerance in Solanum tuberosum - Kiełbowicz-Matuk, Agnieszka; Grądzka, Klaudia; Biegańska, Magdalena; Talar, Urszula; Czarnecka, Jagoda; Rorat, Tadeusz (Frontiers in Plant Science, 2022)
The transition from vegetative growth to reproductive development is a critical developmental switch in flowering plants to ensure a successful life cycle. However, while the genes controlling flowering are well-known in model plants, they are less well-understood in crops. In this work, we generated potato lines both silenced and overexpressed for the expression of StBBX24, a clock-controlled gene encoding a B-box protein located in the cytosol and nuclear chromatin fraction. We revealed that Solanum tuberosum lines silenced for StBBX24 expression displayed much earlier flowering than wild-type plants. Conversely, plants overexpressing StBBX24 mostly did not produce flower buds other than wild-type plants. In addition, RT-qPCR analyses of transgenic silenced lines revealed substantial modifications in the expression of genes functioning in flowering. Furthermore, S. tuberosum lines silenced for StBBX24 expression displayed susceptibility to high salinity with a lower capacity of the antioxidant system and strongly decreased expression of genes encoding Na+ transporters that mediate salt tolerance, contrary to the plants with StBBX24 overexpression. Altogether, these data reveal that StBBX24 participates in potato flowering repression and is involved in salt stress response.